Comparative study of common bean (Phaseolus vulgaris L.) landraces conserved ex situ in genebanks and in situ by farmers - Gómez, O.J.; Blair, Matthew W.; Frankow-Lindberg, BE; Gullberg, U. (Springer, 2005)
Genetic diversity of populations stored ex situ or in situ can be altered due to the management practices they are subjected to. In this paper, we compare populations of two common bean (Phaseolus vulgaris L.) landraces grown on farms with material collected from the same farms and now kept in two ex situ collections (CIAT and REGEN) with the purpose to monitor any changes that have occurred due to ex situ conservation. The diversity was measured using seven bean microsatellite markers. Further phenotypic and developmental traits were registered in a field experiment. Compared with the in situ populations, the ex situ ones had a lower level of gene diversity and we suggest that this is due to the regeneration process. Most of the phenotypic traits did not differ significantly between ex situ and in situ populations, although for yield and 100-seed weight, the CIAT material showed significant lower values. We assume that these populations have gone through an adaptational change. Overall, the conservation ex situ has been successful in maintaining the majority of the adaptations found in the landraces studied, however, the probable loss of genetic diversity that we have observed, suggest that protocols for the regeneration process must be carefully worked out if the majority of alleles are to be preserved for the future. This study also highlights the complementarity of ex situ and in situ conservation methods in order to preserve landrace adaptations and to capture new, useful diversity generated in in situ populations.